2018
DOI: 10.1111/cei.13150
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced TLR2 responses in multiple sclerosis

Abstract: SummaryThe roles of the microbiome and innate immunity in the pathogenesis of multiple sclerosis (MS) remain unclear. We have previously documented abnormally low levels of a microbiome‐derived Toll‐like receptor (TLR)2‐stimulating bacterial lipid in the blood of MS patients and postulated that this is indicative of a deficiency in the innate immune regulating function of the microbiome in MS. We postulated further that the resulting enhanced TLR2 responsiveness plays a critical role in the pathogenesis of MS.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…Although this response is responsible for Aβ clearance, a sustained pro-inflammatory environmental could be detrimental for the host (Heneka et al, 2013; Chen L. et al, 2016; Go et al, 2016). Additionally, TLR2 and TLR7 responses are over-stimulated in PBMCs in MS patients when compared with healthy controls (Hamid et al, 2016; Fujiwara et al, 2018).…”
Section: Cns Inflammation Induced By Hsv-1mentioning
confidence: 99%
“…Although this response is responsible for Aβ clearance, a sustained pro-inflammatory environmental could be detrimental for the host (Heneka et al, 2013; Chen L. et al, 2016; Go et al, 2016). Additionally, TLR2 and TLR7 responses are over-stimulated in PBMCs in MS patients when compared with healthy controls (Hamid et al, 2016; Fujiwara et al, 2018).…”
Section: Cns Inflammation Induced By Hsv-1mentioning
confidence: 99%
“…Upon stimulation using a TLR2 agonist, reduction of Treg function and Th17-like phenotype skewing occurred in MS patients more than in HCs [38]. Enhanced TLR2 responsiveness to its agonist was reported in monocytes and PBMCs of MS patients [31]. The same study found no differences in TLR2 expression in monocytes of MS patients compared to HCs [31].…”
Section: Discussionmentioning
confidence: 88%
“…Enhanced TLR2 responsiveness to its agonist was reported in monocytes and PBMCs of MS patients [31]. The same study found no differences in TLR2 expression in monocytes of MS patients compared to HCs [31]. In the murine model of MS, experimental autoimmune encephalomyelitis (EAE), the lack of TLR2 in CD4 + T cells was shown to ameliorate EAE [32], while inducing TLR2 tolerance via low-levels of a microbiome-derived TLR2 agonist resulted in amelioration of EAE [39].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…A growing body of evidence suggests a role for pattern recognition receptors (PRRs) in autoimmune inflammatory responses (5). Previous studies have primarily focused on Tolllike receptors (TLRs), showing their potential role in modulating pathogenic disease pathways (6)(7)(8); however, little is known about the role of C-type lectin receptors (CLRs) in autoimmunity and particularly in MS (9).…”
Section: Introductionmentioning
confidence: 99%